ANALYSIS OF CONSUMERS PURCHASE MOTIVATION AND DESIRE TO INVEST IN VIRTUAL GOODS ON MASSIVE MULTI PLAYER ONLINE GAMES IN WARNET CEZ – GO MANADO - Kairupan, Reynaldo G. (Universitas Sam Ratulangi, 2019)
Abstract: The digital realm of interaction is a quickly growing and significant part of our lives. It is also becoming an increasingly important target for research and theoretical debate. One area of research that is of particular interest to researchers is online gaming identity practices. If we take a look at the global gaming industry, there is no surprise that the online gaming industry has seen such huge growth. The purpose of this study to analyze the consumers Purchase Motivation and Consumers Desire to invest in virtual goods on Massive Multi-player Online games. This study used qualitative method with in depth interview on respondent. People that play a MMO Games tend to purchase virtual goods because of consumer motivation and desire. People that played MMO Games feels satisfied because the social needs is fulfillment by purchasing the virtual goods inside the Online Games or outside by using real money. People that purchase virtual goods think it as enjoyment for them and can become a profit also in the future. Finally this research recommended to the game developer to usually focus on improve the model of virtual goods for the future study.Keywords: consumer purchase motivation, consumer desire.